ANALISIS PENGARUH UKURAN PERUSAHAAN, ROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ricky Talumantak (LPPM Universitas Asa Indonesia, 2021)
One of the main objective of the company is to increase the share holder wealth by maximizing the value of the firm. The company with good value, which was reflected at their market price, would attract the investor to invest through the capital market or direct investment. This study aims to examines the effect of firm size, profitability and leverage on the firm value. The quantitave research approach was applied on this study by using multiple regression method. The population were infrastrcuture, utility and transportation company which listed on Bursa Efek Indonesia (Indonesian Stock Exchange) with obervation periods between year 2016 to 2019 and purposive sampling method was used to set up the sample. This study found that the firm size, profitability and leverage individually were not proven have a significant effect on the firm value. This study also found that the firm size, profitability and leverage simulatneously was not proven have a significant effect on the firm value